Proof:
Let's Multiply them!
If you don't remember how to multiply matrices, don't worry. In order to get AB we focus on the rows of A, and the columns of B.
- The first row of A is [1 2] and the first column of B is [2/3 1/6], if we do de dot multiplication we get 1(2/3) + 2(1/6) = 2/3 + 1/3 = 1.
- The first row of A is [1 2] and the second column of B is [-1/3 1/6]. Here we get 1(-1/3) + 2(1/6) = -1/3 + 1/3 = 0.
- The second row of A is [-1 4] and the first column of B is [2/3 1/6]. Here we get -1(2/3) + 4(1/6) = -2/3 + 2/3 = 0.
- The second row of A is [-1 4] and the second column of B is [-1/3 1/6]. Here we get -1(-1/3) + 4(1/6) = 1/3 + 2/3 = 1.
Then
We also have to see what happens with
.
With this, we can conclude that
where
is the identity matrix. An by definition, that means that
and
are multiplicative inverses.